Degenerative cervical myelopathy education in UK medical schools: a national cross-sectional survey of medical students. (2nd November 2022) - Brannigan, Jamie F. M.; Davies, Benjamin M.; Stewart, Max; Smith, Sam; Willison, Alice; Ahmed, Shahzaib; Sadler, Iwan; Sarewitz, Ellen; Francis, Jibin; Stacpoole, Sybil R. L.; Kotter, Mark R. N.; Mowforth, Oliver D.
Abstract: Introduction: Degenerative cervical myelopathy (DCM) is a common and progressive neurological condition caused by injury of the cervical spinal cord by degenerative spinal pathology. Delayed diagnosis leading to avoidable and irreversible disability is a major current problem limiting patient outcomes. Lack of sufficient representation of DCM in undergraduate and postgraduate medical curricula may contribute to poor recognition of DCM by non-specialist doctors. The objective of this study was to assess the DCM teaching provision in UK medical schools and the DCM knowledge of UK medical students. Methods: UK medical students completed a web-based survey distributed nationally through university social media pages, university email bulletins and the national student network of Myelopathy.org. The survey comprised a 19-item questionnaire capturing data on student demographics, myelopathy teaching and myelopathy knowledge. Advertisements were repeated monthly over a 12-month recruitment period and participation was incentivised by entry into an Amazon voucher prize draw. Ethical approval for the study was granted by the Psychology Research Ethics Committee, University of Cambridge (PRE.2018.099). Results: A total of 751 medical students from 32 British medical schools completed the survey. Medical students from all year groups participated. Most students (520; 72%) had not received any medical school teaching about DCM. When students had received DCM teaching, the duration of teaching was minimal (75% < 1 h). A total of 350 students (47%) reported conducting private study on DCM. Modal student self-rating of their own knowledge of DCM was ' terrible ' (356; 47%). There was no correlation between a student's subjective rating of their knowledge and their answers to objective questions. A total of 723 (96%) of students expressed interest in learning more about DCM, with lectures the preferred format. Conclusions: DCM appears to be a neglected condition in medical education which has implications for clinical practice. However, student enthusiasm to undertake private study suggests future teaching interventions will be well-received. Future work is necessary to characterise the format of DCM teaching that is most effective and to subsequently measure how educational interventions translate into clinical benefits.